2022
DOI: 10.3390/antiox11081435
|View full text |Cite
|
Sign up to set email alerts
|

Moringa oleifera Leaf Extract Protects C2C12 Myotubes against H2O2-Induced Oxidative Stress

Abstract: The imbalance between reactive oxygen species (ROS) production and antioxidant defense systems leads to macromolecule and tissue damage as a result of cellular oxidative stress. This phenomenon is considered a key factor in fatigue and muscle damage following chronic or high-intensity physical exercise. In the present study, the antioxidant effect of Moringa oleifera leaf extract (MOLE) was evaluated in C2C12 myotubes exposed to an elevated hydrogen peroxide (H2O2) insult. The capacity of the extract to influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…In consistent with previous studies demonstrated the alteration of biochemical markers, hepatic antioxidant status and hepatic nucleic acid content may therefore manifest of oxidative stress and cellular DNA damage caused by CCl4, Enzymatic defence mechanisms such as catalase (CAT), superoxide dismutases (SOD), and gluthatione protect cells from free radical damage (GSH) [15]. As shown in the table(1), we revealed that palm dates increased the levels of glutathione, catalase, and superoxide dismutase when compared to the positive control group Since catalase breaks down hydrogen peroxide into water and oxygen and SOD is in responsible of removing superoxide radicals, these enzymes may help regulate the redox state of plasma.This observation perfectly agrees with those of Ceci et al [16].We focused on the potential chemotherapeutic effects of palm dates in the current study, which may have been mediated through regulating the expression of MMP9 and Caspase3 in an animal model of HCC. Palm date has been used as a herbal remedy for various aliments including cancer by the ancient Arabian, Indian and Chinese cultures .…”
Section: Effect Of Date Fruit Extract and Cisplatin On Histological A...supporting
confidence: 92%
“…In consistent with previous studies demonstrated the alteration of biochemical markers, hepatic antioxidant status and hepatic nucleic acid content may therefore manifest of oxidative stress and cellular DNA damage caused by CCl4, Enzymatic defence mechanisms such as catalase (CAT), superoxide dismutases (SOD), and gluthatione protect cells from free radical damage (GSH) [15]. As shown in the table(1), we revealed that palm dates increased the levels of glutathione, catalase, and superoxide dismutase when compared to the positive control group Since catalase breaks down hydrogen peroxide into water and oxygen and SOD is in responsible of removing superoxide radicals, these enzymes may help regulate the redox state of plasma.This observation perfectly agrees with those of Ceci et al [16].We focused on the potential chemotherapeutic effects of palm dates in the current study, which may have been mediated through regulating the expression of MMP9 and Caspase3 in an animal model of HCC. Palm date has been used as a herbal remedy for various aliments including cancer by the ancient Arabian, Indian and Chinese cultures .…”
Section: Effect Of Date Fruit Extract and Cisplatin On Histological A...supporting
confidence: 92%
“…We previously reported that MIC-1 increases the nuclear translocation of Nrf2, followed by a reduction of oxidative stress and inflammation markers induced by LPS in macrophages [8]. Consistently, moringa leaf extract increased the activities of Nrf2 target enzymes (i.e., superoxide dismutase and catalase) in C2C12 myotubes [22,24]. Therefore, MIC-1's anti-inflammatory properties may also include JAK/STAT, and STING/Nrf2 pathways.…”
Section: Plos Onementioning
confidence: 65%
“…Sulforaphane inhibited NF-κB pathway, including the levels of IL-1β and IL-6, in a genetic model for muscle dystrophy [17]. Also, MIC-1 may improve skeletal muscle health due to its antioxidant effects, as seen in moringa leaf extracts-treated C2C12 cells [21][22][23][24]. For instance, moringa leaf extract reduced oxidative stress induced by hydrogen peroxide in C2C12 myotubes [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were incubated at 37 °C with 5% CO 2 in a humidified atmosphere. Cells were split 1:6 twice weekly and fed 24 h before each experiment [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%